Cooperative Activity as Mediation in the Social Adjustment of Chinese International Students - Ma, Junqian (Journal of International Students, 2018)
Social adjustment is one of the most difficult and long-lasting challenges for international students who study in a new country. This paper uses a case study of cooperative painting activity conducted in Australian setting, in which two Chinese and three other students from different countries participated, in order to assess the efficiency of cooperative activity in mediating the social adjustment of international students. It argues that three factors determine its mediating function: namely, 1) the relaxing, pushy, and thematic setting, 2) the mediator’s role, and 3) communications and interactions. The study provides a new approach to future practices aiming to support the social adjustment of international students.